FUNDAMENTALISM VERSUS SOCIAL INJUSTICE: POLITICAL ECONOMIC DIMENSION OF THE INDONESIAN FUNDAMENTALISM - Lemanto, Eduardus (KRITIS, 2021)
Millennium era has been marked off by the horrific alert of the human extermination one of which is in the cutthroat tragedy of 09/11 in 2001, Indonesia is no exception. The series of terrorist attacks and suicide bombings that have recurred almost every year since 2000 behooves the Indonesian stakeholders to giving their very eyes on the roots of the problem. In Karen Armstrong’s viewpoint, the savagery of that extremist attack that slay thousands of people has nothing to do with religion alone, but dominantly also with economic cliff and political havoc in both national and global level. But she also calls to mind that it does not mean that religion has nothing to do with any barbarous acts. The atrocities in the name of religious motives in some aspects are convincingly the constant implications of the imparity of political economy. Terrorism and the similar acts of villainy instigated by the religious ideology are like “rotting fruit” of its main tree, fundamentalism. Fundamentalism is categorized as one of the huge challenges Indonesia has been facing along the post-Reform era. This article examines the problem of the absence of social justice and multidimensional approach of development at all level as the backbones and the determining factors of the emersion of the Indonesian fundamentalism.